P-186 Wirral end of life care charter. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Gorry, Julie; McGovern, Paul; Fletcher, Jane; Brown, Clare; Thwaites, Annette; Gratwick, Kate; Rice, Liz; Ebrell, Judi; Coulson, Jo; Quinn, Adrian
Abstract : The concept for the creation of a Wirral end of life care charter was born from the necessity for the Wirral Palliative Care and End of Life Care Partnership Group to focus on the need to take stock of a whole range of policy and guideline directives to create and deliver services for patients, their families and carers during the difficult journey through the last year of life and up to the days and hours before death. The challenge was how could we as health and social care providers, patient and carer representatives and commissioners focus on efforts to effectively deliver the levels of quality care and support, with the necessary skills and compassion in a coherent way, and importantly one which patients carers and families and the community of Wirral can relate to. We decided what was needed was a set of pledges in the form of a charter that explains what patients and those close to them may expect from providers of care and support, and of equal importance what providers must do to resource and support staff to deliver first class quality care for palliative patients at the end of their lives. The launch took place with a range of key speakers to both set the scene in terms of supporting Dying Matters Week and to inform as wide an audience as was possible of developments and challenges facing palliative and end of life care in the future. We are proud to say that all Wirral statutory deliverers of health and social care duly signed up and pledged support. "One year on" an endoflifecarewirral.org website has been launched.